PERFORMING RELIGION ON THE SECULAR STAGE - Aronson-Lehavi, Sharon. ([S.l.])
1 online resource
Keywords: This book examines the relations between Western religion, secularism, and modern theater and performance. Sharon Aronson-Lehavi posits that the ongoing cultural power of religious texts, icons, and ideas on the one hand and the artistic freedom enabled by secularism and avant-garde experimentalism on the other, has led theatre artists throughout the twentieth century to create a uniquely modern theatrical hybrid-theater performances that simultaneously re-inscribe and grapple with religion and religious performativity. The book compares this phenomenon with medieval forms of religious theater and offers deep and original analyses of significant contemporary works ranging from plays and performances by August Strindberg, Hugo Ball (Dada), Jerzy Grotowski, and Hanoch Levin, to those created by Adrienne Kennedy, Rina Yerushalmi, Deb Margolin, Milo Rau, and Sarah Ruhl. The book analyzes a new and original historiography of a uniquely modern theatrical phenomenon, a study that is of high importance considering the reemergence of religion in contemporary culture and politics.